Le charme discret of remnant movement: crossing and nesting in Polish OVS sentences - Wiland, Bartosz (Studies in Polish Linguistics, 2016)
Remnant movement, once believed not to be a part of grammar at all, has since become a tool of analyzing phenomena like verb fronting, word order alternations, or covert movement. What has been largely missing from the discussion of remnant movement are the effects a remnant constituent has on the nodes in the clause it has crossed. This paper argues that remnant movement has particular consequences for clausal syntax since it gives rise to crossing and nesting movement dependencies. This point is illustrated on the example of certain robust asymmetries in the Polish OVS syntax. The analysis of Polish OVS sentences has a broader benefit, namely that the proper identification of crossing and nesting paths provides convergent evidence for the existence of remnant movement in the first place.
Keywords: word order; OVS; remnant movement; smuggling; binding; weak crossover; extraction; cartography